2021
DOI: 10.1017/s0025315420001356
|View full text |Cite
|
Sign up to set email alerts
|

A review of cephalopods (Phylum: Mollusca) of the Canary Current Large Marine Ecosystem (Central-East Atlantic, African coast)

Abstract: An extensive review of cephalopod fauna in the Central and North Atlantic coast of Africa was performed based on material collected during 10 research cruises in these waters. In the Canary Current Large Marine Ecosystem (CCLME) area, a total of 378,377 cephalopod specimens was collected from 1247 bottom trawl stations. Of those specimens, 300 were sampled for subsequent identification in the laboratory and found to belong to 65 different species and 23 families. After an exhaustive review of the existing lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Some preys were recognized by their components, such as otoliths, scales and vertebras for Teleostei; antennas, shells and appendages for crustaceans, whereas cephalopods group was spotted by the remains of beaks, mantles suckers and tentacles. Based on identification keys (Reiss et al, 2009;Marceniuk et al, 2017;Luna et al, 2021), Table (1) shows the list of preys' items identified based on stomach content analysis. Identification of all preys ingested, identified abiotic materiel (IAM) and unidentified abiotic materiel are displayed in Table (1).…”
Section: Resultsmentioning
confidence: 99%
“…Some preys were recognized by their components, such as otoliths, scales and vertebras for Teleostei; antennas, shells and appendages for crustaceans, whereas cephalopods group was spotted by the remains of beaks, mantles suckers and tentacles. Based on identification keys (Reiss et al, 2009;Marceniuk et al, 2017;Luna et al, 2021), Table (1) shows the list of preys' items identified based on stomach content analysis. Identification of all preys ingested, identified abiotic materiel (IAM) and unidentified abiotic materiel are displayed in Table (1).…”
Section: Resultsmentioning
confidence: 99%
“…Within the Chtenopterygidae family, only Chtenopteryx sepioloides and C. sicula have been confirmed as bioluminescent, for which the large eyeball photophores can assist in identifying these species (Escańez et al, 2012;Escańez et al, 2018;Luna et al, 2021). The potential presence of photophores in C. canariensis remains debated (Escańez et al, 2012;Escańez et al, 2018;Luna et al, 2021).…”
Section: Bathyteuthidamentioning
confidence: 99%
“…Cephalopods are exclusively marine molluscs that includes nautilids, cuttle shes, squids, and octopods, with around 860 species distributed in 50 families and 174 genera (Hoving et al 2014; Luna et al 2021), some species are large animals that can have wide geographical distributions (> 5,000 km) (Rosa et Since all cephalopods have funnel and jet propulsion, the size and shape of ns could be determinant in their movement capabilities (Clarke 1988). Squids have nine different n shapes that contribute to fast swimming and orientation control (following Clarke 1988; Boyle and Rodhouse 2005).…”
Section: Introductionmentioning
confidence: 99%